Effects of Gasoline Price Changes On Short Term Market Behavior Of Energy And Non-Energy Sector: Evidence From Saudi Arabia - Shahid, Humera; Mahmood, Faiq; Usman, Muhammad (International Journal of Energy Economics and Policy, 2017)
The gasoline prices are highly regulated in Saudi Arabia however due to economic reforms government has decided to increase the gasoline and other energy prices in different times in the coming five years. This study aims to analyze the impact of domestic gasoline price change on stock market performance of energy and non-energy sectors of the Saudi Arabia. The study has developed hypothesis and used event study methodology. Findings show that in short run increase in gasoline prices has negative effects on market performance of non-energy sector for which gasoline is a major unit in cost of production. The study results are more true for such non energy sector who could easily shift its increased cost to customers by increasing its product prices e.g. transportation sector. However, the study could not find any such evidences in the energy sector. These findings are of great implication to researchers, government regulatory bodies, and other stakeholders of stock markets. Keywords: Economic Reforms, Gasoline Prices, Event study methodology, Tadawul Stock Exchange JEL Classifications: E3, G1, P11, O13, L78